Pembelajaran problem based learning (PBL) dengan kerangka kerja TPaCK: kemampuan pemecahan masalah matematis siswa SMA - Pratidina, Dian Aliza; Nindiasari, Hepsi (IKIP Siliwangi, 2023)
This research was conducted to investigate the influence of PBL (Problem-Based Learning) with the TPaCK framework on the mathematical problem-solving abilities of high school students, specifically focusing on the topic of Systems of Linear Equations with Three Variables (SPLTV). The study employed a pre-experimental design using a one-group pretest-posttest approach at a public high school in Kabupaten Serang with Class X IPA 6 as the selected research sample. The participants were chosen through purposive sampling during the first semester of the academic year 2022–2023. Data collection in this study involved pre-tests and post-tests. The data obtained from the initial and final tests was then processed through three stages, namely descriptive data analysis, data prerequisite test, and hypothesis test The findings of this research demonstrate that PBL with the TPaCK framework can enhance the mathematical problem-solving abilities of high school students.